Laser ablation and photostimulated passivation of Cd₁₋ₓZnₓTe crystals - Zagoruiko, Yu.A.; Fedorenko, O.A.; Khristyan, V.A.; Kovalenko, N.O.; Mateychenko, P.V.; Dobrotvorskaya, M.V.; Poluboyarov, A.A. (Functional Materials, 2012)
Proposed is a new technology of passivation of Cd₁₋ₓZnₓTe crystals which comprises preliminary treatment of their surface by laser ablation aimed at removal of the disturbed surface-adjacent layer arising due to mechanical treatment (cutting, grinding, polishing) of the samples. Degradation of the spectrometric characteristics of the detectors after chemical etching is compared with their degradation caused by the proposed passivation method.